RSIPS: A Robust System to Identify Phishing Websites using Unique Addressing features of Web - Karamchand Gandhi, V; Suriakala, M (International Journal of Computer Sciences and Engineering, 2025)
Phishing is a form of internet fraud in which an attacker, also known as a phisher, attempts to fraudulently retrieve legitimate users' confidential or sensitive credentials by imitating electronic communications from a trustworthy or from the public organization in an automated fashion. There is an need of identify the phishing websites in this emerging digital era. Based on the URL and content based features of websites like length of URL, domain’s age, WHOIS properties, etc, we can draw an algorithm to identify the phishing websites. Furthermore, our approach checks the legitimacy of a webpage using hyperlink features. Hyperlinks are extracted from the source code of the given website and apply that into the proposed algorithm to detect phishing site. Our experiment shows that our proposed algorithm is very effective to detect the phishing websites and it have 89.16% True Positive Rate while greater than 82% of accuracy.